A relook into the life of Hendrick Hamel and various editions of “Hamel’s Journal” - Goh, Cleo (International Journal of Korean Humanities and Social Sciences, 2022)
It is undisputed that Hamel is known in Korea’s history as a historical character who first introduced Joseon to the West in the 17th century. Prior to the release of Hamel’s Journal, the West had never heard of a country named Joseon. Furthermore, Hamel’s Journal also was significant as one of the only sources of information the West had of Joseon up till the 19th century. However, there are still misunderstandings surrounding the historical significance of Hamel in Korea’s history, and additionally, the impact of Hamel’s Journal in the West is not as well-studied despite having played such an important role. Therefore, this paper aims to first look into the historical significance of Hamel within Korea’s history and resolve the misunderstandings surrounding it. Also, the impact of Hamel’s Journal in the West will be discussed and what its role was in shaping the West’s perspective of Joseon from the 17th century.